2015
DOI: 10.1371/journal.pgen.1004932
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Toll-like Receptor Signaling by the SF3a mRNA Splicing Complex

Abstract: The innate immune response plays a key role in fighting infection by activating inflammation and stimulating the adaptive immune response. However, chronic activation of innate immunity can contribute to the pathogenesis of many diseases with an inflammatory component. Thus, various negatively acting factors turn off innate immunity subsequent to its activation to ensure that inflammation is self-limiting and to prevent inflammatory disease. These negatively acting pathways include the production of inhibitory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 145 publications
0
50
1
Order By: Relevance
“…Alternative splicing can impact cellular function by creating distinct mRNA transcripts from the same gene, which may encode unique proteins that have distinct or opposing functions. For instance, in human and mouse cells, several alternatively spliced forms of genes involved in the TLR pathway have been shown to function as negative regulators of TLR signaling in order to prevent uncontrolled inflammation [9][10][11]. Additionally, several in-depth studies of individual genes suggest that alternative splicing plays an important role in increasing the diversity of transcripts encoding MHC molecules [12] and in modulating intracellular signaling and intercellular interactions through the expression of various isoforms of key cytokines [13,14], cytokine receptors [9,15,16], kinases [17] and adaptor proteins [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Alternative splicing can impact cellular function by creating distinct mRNA transcripts from the same gene, which may encode unique proteins that have distinct or opposing functions. For instance, in human and mouse cells, several alternatively spliced forms of genes involved in the TLR pathway have been shown to function as negative regulators of TLR signaling in order to prevent uncontrolled inflammation [9][10][11]. Additionally, several in-depth studies of individual genes suggest that alternative splicing plays an important role in increasing the diversity of transcripts encoding MHC molecules [12] and in modulating intracellular signaling and intercellular interactions through the expression of various isoforms of key cytokines [13,14], cytokine receptors [9,15,16], kinases [17] and adaptor proteins [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Our prior studies indicated that inhibiting SF3A1 altered splicing of many genes in the TLR signaling pathway, 5 including the signaling adaptor MyD88. The MyD88 gene encodes two isoforms: a long isoform (MyD88L, an NFκB activator), and a shorter isoform in which exon two is skipped (MyD88S, an NFκB inhibitor).…”
mentioning
confidence: 99%
“…The PCR products 4 were then resolved using agarose gel electrophoresis. This also allowed us to determine the relative levels of the two isoforms, as there is substantially more MyD88-L than MyD88-S in unstimulated cells (12,33). In the absence of LPS, only a single PCR product of 369 bp corresponding to MyD88-L was amplified (Fig.…”
Section: Lps Induces Myd88-s Expression In Mouse Macrophagesmentioning
confidence: 99%
“…MyD88-L was assessed using a forward primer that annealed to the exon 2-3 boundary and a reverse primer that annealed to exon 3; MyD88-S was assessed using a primer that annealed to the unique exon 1-3 boundary and a reverse primer that annealed exon 3. These MyD88 isoform-specific primers as well as primers used to analyze cytokines and housekeeping genes have been validated extensively by us previously (12,33,71). RT-PCR to analyze MyD88-L and MyD88-S simultaneously was performed by first reverse transcribing RNA with the iScript cDNA synthesis kit (Biorad) and subsequently performing PCR using primers that bracket exon 2 (Table S1).…”
Section: Qpcr Rt-pcr and Elisa Analysismentioning
confidence: 99%
See 1 more Smart Citation